Status Meiotik oosit kucing setelah masturasi in vitro pada waktu yang berbeda - S. Gustari; S. Budhi; F. Indrafuri; N.W.K Karja (Hemera Zoa, 2009)
The purpose of the research was to determine meiotic status of cat oocytes maturated in vitro at various duration times. Cat ovaries were collected from sexually mature queens after routine ovariohysterectomy. Oocytes were collected from those ovaries by slicing method and only good oocytes were maturated in maturation medium and incubated at 38,5oC in 5% CO2 humidified incubator in various duration. The durations were at 18-20 hours, 22-24 hours and 28-30 hours. At the end of maturation, the oocytes were fixed and stained with acetic orcein. The percentage of oocytes that reached metaphase II for 18-20 hours, 22-24 hours and 28-30 hours maturation were 60% ± 0.04 ; 68% ± 0.31 and 77% ± 0.2, respectively. There were no significant differences (P>0.05) on the percentage of oocytes in reaching the stage of germinal vesicle, anaphase-telophase and methapase II. Keywords : in vitro maturation, cat oocytes and meiotic status of the oocytes.